Leptin as a mediator between obesity and cardiac dysfunction - Joanna Karbowska (Postępy Higieny i Medycyny Doświadczalnej, 2012)
Obesity is now recognised as one of the most important risk factors for heart disease. Obese individuals have high circulating levels of leptin, a hormone secreted by adipose tissue and involved in energy homeostasis. Growing evidence suggests that leptin may contribute to the development of cardiac dysfunction. In a large prospective study leptin has been shown to be an independent risk factor for coronary heart disease. An independent positive association has also been found between plasma leptin levels and heart rate in hypertensive patients and heart transplant recipients. In animal studies chronic leptin infusion increased heart rate and blood pressure. It has also been demonstrated that circulating leptin levels are elevated in patients with heart failure. The level of plasma leptin was associated with increased myocardial wall thickness and correlated with left ventricular mass, suggesting a role for this hormone in mediating left ventricular hypertrophy in humans. Moreover, leptin directly induced hypertrophy and hyperplasia in human and rodent cardiomyocytes, accompanied by cardiac extracellular matrix remodelling. Leptin may also influence energy substrate utilisation in cardiac tissue.These findings suggest that leptin acting directly or through the sympathetic nervous system may have adverse effects on cardiac structure and function, and that chronic hyperleptinaemia may greatly increase the risk of cardiac disorders. Additional studies are needed to define the role of leptin in cardiac physiology and pathophysiology, nevertheless the reduction in plasma leptin levels with caloric restriction and weight loss may prevent cardiac dysfunction in obese patients.